INVESTIGATION OF STRESS STATE IN THE ELEMENTS OF RAIL FASTENINGS, TYPE KPP-5 UNDER THE INFLUENCE OF ROLLING STOCK - Nastechik, M. P.; Bondarenko, I. O.; Marcul, R. V. (Science and Transport Progress, 2015)
Purpose. To date, there is a tendency for the implementation of high-speed trains on the territory of the Ukrainian Railways, which requires increasing the strength and stability of the construction of the railway track. At the same time requirements for intermediate rail fastening have increased and widened. It is on trackwork and repair of the rail fastening labor costs during the operation are from 10 to 18%. One of the main types of fastening, which after long operational observations was included in the permanent operation (5 th. km.) is an intermediate fastening, type КПП-5. Data from previous theoretical studies reliably prevented clear science-based answers and results of the rail fastening. Therefore, the aim is to develop a methodology and rationale for the theoretical research work of rail fastening, type КПП-5 with a detailed assessment of the appearance of stress state places in its elements from the effects of rolling stock. Methodology. The basis of study methods of theoretical research work of the intermediate rail fastening, type КПП-5 (with a detailed assessment of the state of stress in its intermediate elements from the effects of the rolling stock) is the theory of finite elements method (FEM). Findings. Using the FEM it was found that one of the main elements of the intermediate rail fastening, which first perceives share of the value of the lateral force transmitted from the effects of rolling stock are elastic type terminals, type КП-5. Analyzing the data set, the bars in the terminal voltages at the inner side of the rail thread 53,1-56% are greater than the stresses on the outside of rail thread. Originality. A mathematical model of railway track with intermediate rail fastening, type КПП-5 under the action of rolling stock for the study of the stress state in the elements of fastening was developed. This mathematical model let take into account the physical and mechanical properties of the test elements and geometrical fixing fastenings as constructive and operational characteristics of the entire rail fastening in general. Practical value. The obtained results in this work of FE simulations allow reflecting and exploring the most likely places of the stress state appearance in the elements of the fastening, type КПП-5, in which damages and defects can be in the future. This in general will affect the operation stability of the railway track as a whole.